2006
DOI: 10.1016/j.ymthe.2005.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity and Loss of Disease Site Targeting Caused by Antibody Responses to PEGylated Liposomes

Abstract: The systemic application of nucleic acid drugs requires delivery systems that overcome the poor pharmacokinetics, limited biodistribution, and inefficient uptake of nucleic acids. PEGylated liposomes show considerable promise because of their intrinsic ability to accumulate at disease sites and facilitate transfection of target cells. Unlike many viral vectors, PEGylated liposomes are generally considered to be nonimmunogenic. We have developed a PEGylated liposome for the systemic administration of plasmid DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
167
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(174 citation statements)
references
References 45 publications
(76 reference statements)
7
167
0
Order By: Relevance
“…The ABC phenomenon was also reported with other PEGylated lipid nanoparticles containing pDNA [49] . Judge and colleagues [49] reported that stable plasmid lipid particles (SPLPs) incorporating PEG-S-DSG (a PEGylated lipid containing a C18 alkyl chain) or PEG-S-DPG (C16) increased serum levels of anti-PEG IgM, which in turn reduced gene transfection activity in the tumor by ∼ 10-fold for the second injection.…”
Section: Diffusive Pegylated Nanoparticles Avoid the Abcsupporting
confidence: 73%
See 1 more Smart Citation
“…The ABC phenomenon was also reported with other PEGylated lipid nanoparticles containing pDNA [49] . Judge and colleagues [49] reported that stable plasmid lipid particles (SPLPs) incorporating PEG-S-DSG (a PEGylated lipid containing a C18 alkyl chain) or PEG-S-DPG (C16) increased serum levels of anti-PEG IgM, which in turn reduced gene transfection activity in the tumor by ∼ 10-fold for the second injection.…”
Section: Diffusive Pegylated Nanoparticles Avoid the Abcsupporting
confidence: 73%
“…Judge and colleagues [49] reported that stable plasmid lipid particles (SPLPs) incorporating PEG-S-DSG (a PEGylated lipid containing a C18 alkyl chain) or PEG-S-DPG (C16) increased serum levels of anti-PEG IgM, which in turn reduced gene transfection activity in the tumor by ∼ 10-fold for the second injection. However, when the acyl chain length of the PEGylated lipid was reduced to C14 (PEG-S-DMG), the resulting SPLPs only induced mild increases in serum levels of anti-PEG IgM (only 1/3 or less compared to the C16 and C18 SPLPs).…”
Section: Diffusive Pegylated Nanoparticles Avoid the Abcmentioning
confidence: 99%
“…PEG-lipids with longer acyl chain confer stronger interaction with membrane lipids thus less likely to be extracted/exchanged, and consequently, PEGs with longer lipid anchor are often associated with a slower rate of deshielding (15,(19)(20)(21). Our results suggest that PEG-DMPE may be shed rapidly to expose the "naked" lipid particle consisting of fusogenic lipid D-Lin-DMA, which allows it to fuse with the cell membrane to achieve efficient siRNA transfection in vitro.…”
Section: Discussionmentioning
confidence: 83%
“…It consists of cholesterol, DSPC, D-Lin-DMA and PEG-C-DMA. Among these components, the neutral lipids DSPC and cholesterol are commonly used in many liposome formulations for maintaining liposome structure whereas PEG-C-DMA and DLin-DMA are unique components of SNALP that are critical for its in vivo delivery efficiency (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is important to note that no adverse reactions were observed in the animals from the final 3-mg/kg dose when antibodies were present. This result contrasts with the adverse reactions observed with repeated administration of lipid-based systems that are associated with the presence of antibodies (22,23,(25)(26)(27)(28).…”
Section: Multiple Doses Of Targeted Nanoparticles Safely Administered Inmentioning
confidence: 60%